Acoustic Sensor Design for Dark Matter Bubble Chamber Detectors - Ivan Felis; Juan Antonio Martínez-Mora; Miguel Ardid (Sensors, 2016)
Dark matter bubble chamber detectors use piezoelectric sensors in order to detect and discriminate the acoustic signals emitted by the bubbles grown within the superheated fluid from a nuclear recoil produced by a particle interaction. These sensors are attached to the outside walls of the vessel containing the fluid. The acoustic discrimination depends strongly on the properties of the sensor attached to the outer wall of the vessel that has to meet the requirements of radiopurity and size. With the aim of optimizing the sensor system, a test bench for the characterization of the sensors has been developed. The sensor response for different piezoelectric materials, geometries, matching layers, and backing layers have been measured and contrasted with FEM simulations and analytical models. The results of these studies lead us to have a design criterion for the construction of specific sensors for the next generation of dark matter bubble chamber detectors (250 L).